COMPARATIVE STUDY ON ANTIMICROBIAL ACTIVITY OF TULSI (OCIMUM SANCTUM) AND NEEM (AZADIRACHTA INDICA) METHANOL EXTRACT - Kumar, Vipul; Chakraborty, Anurag; Kaur, Manpreet; Pandey, Sony; Jena, Manoj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was focused on to compare the antimicrobial activity of methanolic leaf extracts of tulsi and neem. Methods: We have chosen tulsi (Ocimum sanctum) and neem (Azadirachta indica) to compare their antimicrobial activity toward Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. Phytochemical extracts have been made by the use of methanol as solvent and dried leaf powder by the cold maceration extraction process. Phytochemical analysis for some secondary metabolites has been done using standard protocols. Nutrient agar plates were inoculated with the above-mentioned microorganisms by spreading bacterial inoculum on the surface of the media. Wells (6 mm in diameter) were punched in the agar. The phytochemical extracts of neem and tulsi were allowed to diffuse into the medium, and after incubation of 24 h at 37Â°C, the zones of inhibition were observed. Results: Statistical analysis showed that tulsi was more effective toward S. aureus while neem was more effective toward E. coli. Minimum inhibitory concentration (MIC) of tulsi for both the microorganisms was 0.4 g/ml, and the MIC of neem for both the microorganisms was 0.2 g/ml. When both the tulsi and neem extract were mixed with each other for every concentration at equal volume, they have shown better effects in comparison to individual neem or tulsi extract and also the MIC got reduced to 0.2 g/ml for both the bacteria. Conclusions: Leaf extracts of both the A. indica and O. sanctum have shown antimicrobial activity against E. coli and S. aureus. A. indica has higher antimicrobial activity against S. aureus, whereas the O. sanctum was found to be more effective against E. coli (indicated by the zone of inhibition). When both the extracts were mixed with each other, they have shown a better effect toward both bacteria.